2019
DOI: 10.12669/pjms.35.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase is a predictor of Bone Mineral Density in postmenopausal females

Abstract: Objectives: The study was planned to determine whether serum calcium, phosphate and alkaline phosphatase (ALP) are predictors of bone mineral density (BMD) in postmenopausal non-osteoporotic, osteopenic, and osteoporotic females. Methods: In this cross sectional study, conducted at Shaikh Zayed Hospital, Lahore in the year 2014-2015, postmenopausal females between 50-70 years of age were taken and divided into three groups non-osteoporotic (n=52), osteopenic (n=69) and osteoporotic (n=47). Serum ALP, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
1
29
0
1
Order By: Relevance
“…The analysis of enrolled patients' comorbidities excluded that circulating PTX3 levels could be modulated by an inflammatory component. Elevated ALP levels have been detected in postmenopausal OP women and OP men, and it has been proposed that serum ALP levels could be used as an index of decreased bone mineral density [35][36][37]. In addition, an increased expression of PTH levels causes an up-regulation of RANKL, which in turn leads to an unbalance of remodelling processes and bone resorption, a condition that predisposes to OP development [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of enrolled patients' comorbidities excluded that circulating PTX3 levels could be modulated by an inflammatory component. Elevated ALP levels have been detected in postmenopausal OP women and OP men, and it has been proposed that serum ALP levels could be used as an index of decreased bone mineral density [35][36][37]. In addition, an increased expression of PTH levels causes an up-regulation of RANKL, which in turn leads to an unbalance of remodelling processes and bone resorption, a condition that predisposes to OP development [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding osteocalcin, an osteoblast-specific secreted protein expressed by mature osteoblasts, the observed increase is not surprising because it is used in clinical practice and in research as a marker of bone turnover [ 74 ]. The same meaning should have the age-related increase in ALP mostly due to female gender [ 75 ]. The low levels of calcium observed in LLIs are likely linked to low levels of vitamin D due to inadequate consumption or exposure to sunlight [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have shown that long-term estrogen deficiency increased both bone resorption and bone formation markers in postmenopausal women, suggestive of enhanced bone turnover with increased net bone loss [ 88 , 89 , 90 , 91 ]. Estrogen deficiency increases renal calcium excretion while decreasing intestinal calcium absorption [ 10 ], and the resultant fall in calcium levels can activate various bone resorption mechanisms that include PTH, osteocalcin, OPG, and the RANK/RANKL system [ 91 , 92 , 93 , 94 , 95 ]. These bone resorption markers are, therefore, found in the blood in higher concentrations in osteoporosis.…”
Section: Postmenopausal Osteoporosis: a Silent Diseasementioning
confidence: 99%